Neurologic Complication Due to Crystallization After Drug Interaction Between Alkalized Lidocaine and Ropivacaine: A Case Report and in vitro Study - Zhu, Afang; Pei, Lijian; Liu, Wei; Cheng, Wencong; Zhang, Yu; Huang, Yuguang (Frontiers in Medicine, 2022)
Background For pregnant women transferred to emergency cesarean section after receiving epidural labor analgesia, there is still a debate over the effective and safe means of rapidly delivering surgical anesthesia. Alkalized lidocaine is often adopted for fast onset time; however, crystallization of the anesthetic may cause severe neurologic symptoms. Case Presentation We report a case of a pregnant woman who underwent emergency cesarean section with satisfied analgesia but experienced severe weakness and paranaesthesia in the lower limb. After excluding lumbar disc herniation, obstetric nerve injury, and anesthesia technique causes by symptoms signs and magnetic resonance imaging, drug-related injury became the most likely cause. Our in vitro testing confirmed the obvious precipitation of additional anesthetic-concentrated ropivacaine (0.5–1%) with pretreated alkalized lidocaine. With trophic neurotherapy, the parturient attained prompt relief of weakness by day four, but delayed recovery of numbness, which lasted for 4 weeks. Conclusion To date, this is the first case reporting neurologic complication possibly due to drug crystallization in cesarean section. Our study confirmed the rapid onset of alkalized lidocaine and its safety to pretreated routine labor dose of ropivacaine (0.09%). However, additional anesthetic-concentrated ropivacaine (0.5–1%) to maintain the anesthesia and analgesia level is not suggested.